2020
DOI: 10.22515/tabasa.v1i1.2607
|View full text |Cite
|
Sign up to set email alerts
|

Pola Karakteristik Ragam Bahasa Istilah Pada Masa Pandemi Covid 19 (Coronavirus Disease 2019)

Abstract: The term is a form of words or a combination of words used to express a concept to get a certain meaning. This study aims to describe the characteristic patterns of various language terms during the Covid pandemic 19. This research uses a qualitative descriptive approach where the results of the analysis are described in words but not in numerical form. The subjects in this study used new terms that existed during the Covid pandemic 19. While the object in this study was a characteristic pattern focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
0
13
0
10
Order By: Relevance
“…Penelitian tentang ragam bahasa telah dilakukan oleh para penelitia terdahulu yaitu (Oktavia, 2020) dan (Handika, 2019). Para peneliti melakukan penelitian tentang variasi bahasa yang muncul saat masa pandemic covid-19 yaitu ragam bahasa pada siswa dalam komunikasi verbal dan bahasa remaja pada mahasiswa.…”
Section: Pendahuluanunclassified
“…Penelitian tentang ragam bahasa telah dilakukan oleh para penelitia terdahulu yaitu (Oktavia, 2020) dan (Handika, 2019). Para peneliti melakukan penelitian tentang variasi bahasa yang muncul saat masa pandemic covid-19 yaitu ragam bahasa pada siswa dalam komunikasi verbal dan bahasa remaja pada mahasiswa.…”
Section: Pendahuluanunclassified
“…Kajian tentang aspek kesantunan dan ragam bahasa telah dijalankan oleh pengkaji seperti Fujiastuti (2014), Oktavia & Hayati (2020), Sitorus (2018), Rahayu (2012) dan Zullina & Maulida (2019).Walau bagaimanapun, dapatan kajian mereka ini tidak menghubungkaitkan penggunaan bahasa itu dengan grid etnografi komunikasi Hymes (1972). Kajian tersebut hanya menganalisis pengaruh faktor sosial, faktor demografik dan pemprosesan penggunaan bahasa semasa masyarakat menggunakan bahasa dalam media sosial.…”
Section: Pendahuluanunclassified
“…The meaning of the term is more fixed, definite, and precise. In addition, the term is only used in certain fields of activity (Chaer, 2009, p. 52(. Many studies were conducted on the formation of terms, such as that conducted by (Okavia & Hayati, 2020(. It indicated that there were four types of language terms found.…”
Section: Kesimpulanmentioning
confidence: 99%